Success and failure in the operational recruitment process: Contrasting the outcomes of search - Martina Rebien; Alexander Kubis; Anne Müller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
Following microeconomic theory, every vacancy should be filled by appropriate manpower after a certain time. However, from an empirical point of view it is evident that vacancies remain unfilled as establishments cancel their search for a suitable applicant. The German Job Vacancy Survey (JVS) is a representative survey of job offers for the entire German economy and provides information about the search and matching processes for both the establishments' most recent hires and for failures in the recruitment processes. The analysis is based on a binary explanatory variable, resulting from the interaction of individual successful and unsuccessful search processes (cancellation probability). Our results show that with increasing recruitment duration, the number of search cancellations becomes more likely. Moreover, the results indicate that the probability of a search cancellation is strongly linked to the characteristics that an applicant must provide and to the way the search is organised. – – In der Theorie sollte jede offene Stelle über kurz oder lang durch eine geeignete Arbeitskraft besetzt werden. Aus empirischer Sicht zeigt sich jedoch, dass offene Stellen unbesetzt bleiben, wenn Firmen die Suche nach einem geeigneten Kandidaten aufgeben. Die IAB-Stellenerhebung (IAB-SE) ist eine repräsentative Betriebsbefragung zu offenen Stellen und Stellenbesetzungsprozessen in Deutschland. Sie bietet Informationen sowohl zu aktuellen Stellenbesetzungen als auch zu erfolgloser Bewerbersuche. Die Analyse stützt sich dabei auf eine binäre abhängige Variable die für einen bestimmten Betrieb die erfolgreiche und nicht erfolgreiche Personalsuche identifiziert (Abbruchwahrscheinlichkeit). Unsere Ergebnisse zeigen, dass eine längere Dauer der Personalsuche zu einer höheren Wahrscheinlichkeit von Abbrüchen führt. Zudem wird deutlich, dass ein Abbruch der Personalsuche stark mit den Anforderungen, die ein Kandidat für die offene Stelle aufweisen muss und der Art und Weise wie die Personalsuche organisiert ist, zusammenhängt.
Keywords: J23; J63; D22; 330; establishment survey; job vacancies; labour demand